The Impact of Entrepreneurship Programs On the Economic Empowerment of Rural Women in Vidarbha, Maharashtra: Exploring the Impact of Entrepreneurship Programs on Rural Women's Economic Empowerment in Vidarbha, Maharashtra (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Women entrepreneurs are playing a significant role in today's society and are now asignificant component of the global economic community. For long-term economic growth andsocial advancement, women's participation in entrepreneurship is crucial. Despite playing a significantpart in Indian society, women's entrepreneurial potential has not yet been fully realized because of theirinferior social position. Rural women entrepreneurs have even more low social status than urban one.The goal of the current study is to strengthen rural women by creating industrial facilities based on thelocal expertise.Thus, the study focuses on impact of EDP on rural women status. It also focuses on the reasons whywomen choose to become entrepreneurs. 90 women aged 16 to 40 were chosen for the study inVidarbha, Maharashtra. All of them had a skill-upgrading programme created with the existing skills ofrural women in account. Self-made questionnaire, survey was used to gather primary data. Comparativeanalysis had been done to find out impact of Entrepreneurship development program (EDP) on ruralwomen entrepreneurs. Analysis of their skills, income, savings, freedom of mobility, appreciation fromfamily and of personal profile had been done. Results were displayed in the form of tables, bar graphs.The study's main objective is to empower rural women by creating a EDP for rural women